Post-conditioning with lipopolysaccharide reduces the inflammatory infiltrate to the injured brain and spinal cord: a potential neuroprotective treatment. - Davis, A; Campbell, S; Wilainam, P; Anthony, D (2005)
Systemic infection often accompanies or precedes acute brain injury, but it remains unclear how the systemic response contributes to outcome. To examine this problem we have microinjected recombinant interleukin-1beta (IL-1beta), a cytokine associated with acute brain injury, into the rat brain parenchyma and either preceded or followed this challenge with the intravenous injection of lipopolysaccharide (LPS), which mimics systemic inflammatory response syndrome. The microinjection of IL-1beta alone into the brain parenchyma gives rise to leukocyte mobilization in the blood, and to the delayed recruitment of neutrophils and monocytes to the brain with no evidence of blood-brain barrier breakdown or overt neuronal cell death. Systemic LPS pre-conditioning resulted in a dose-dependent reduction both in the number of circulating leukocytes and in the number of leukocytes recruited to the brain parenchyma after 12 h. Surprisingly, LPS given two hours after injury was equally effective in reducing the recruitment of leukocytes to the brain, which is more relevant to the management of clinical disease. In a more clinically relevant model of spinal cord injury, intravenous LPS post-conditioning also reduced the numbers of leukocytes mobilized in the blood and recruited to the spinal cord and thus limited the breakdown of the blood-spinal cord barrier. The effects appear to be specific to LPS, as they were not observed after intravenous IL-1beta pre-conditioning. Our studies suggest that individual pro-inflammatory conditioning strategies may protect the injured central nervous system from the damaging consequences of leukocyte recruitment and may provide scope for novel therapeutic intervention.